Understanding the effects of war-related trauma and deployment on the couple relationship: evidence for the Couple Adaptation to Traumatic Stress (CATS) model - Wick, Stephanie (Kansas State University, 2010)
The purpose of the current study is to understand the lived experiences of military couples regarding the effects of war-related trauma and deployment on couple functioning. An interpretive phenomenological perspective was utilized during data analysis. This type of phenomenological perspective suggests that human phenomena can only be understood in a situated context (Packer & Addison, 1989). This is to suggest that a person’s emotions, behaviors, and experiences cannot be separated from the context in which they occur. For the purpose of this study, the “context” under consideration was the Army culture and customs in which each of the participant couples was embedded. The Couple Adaptation to Traumatic Stress Model (CATS; Nelson Goff & Smith, 2005) offers a constructive step forward in systemically understanding and treating the impediments created by war-related trauma and deployment. The current study utilized the core terms included in the CATS Model (Nelson Goff & Smith, 2005) as sensitizing concepts to guide the qualitative analysis process. This includes the CATS Model couple functioning variables of attachment, satisfaction, stability, adaptability, support/nurturance, power, intimacy, communication, conflict, and roles. Using qualitative interviews from 90 participants (n = 45 couples), five themes were identified as salient, including communication, conflict management, roles, support/nurturance, and post-traumatic growth. Participants were divided into subgroups (n = 15 couples, 30 total participants) according to their scores on the Purdue Post-Traumatic Stress Disorder Scale – Revised (PPTSD-R; Lauterbach & Vrana, 1996) and the Dyadic Adjustment Scale (DAS; Spanier, 1976). This subsample was selected to examine differences in themes among couples with high and low levels of marital satisfaction, as well as those with high and low levels of post-traumatic stress symptoms. Many similarities were found among the couples with high marital satisfaction and those with low levels of post-traumatic symptoms. Likewise, similarities were also discovered among the couples with lowest levels of marital satisfaction and those with highest levels of post-traumatic stress symptoms. From the current study, there is clear evidence in support of the CATS Model elements of communication, conflict, roles, support/nurturance, and satisfaction. A new contribution to the CATS Model can be made from the current study, which is the inclusion of post-traumatic growth.
Keywords: War-Related Trauma; Deployment; CATS Model; couple functioning; Health Sciences, Mental Health (0347)